Investigation of the Passivation Properties of the Solid Electrolyte Interphase Using a Soluble Redox Couple. Issue 5 (5th February 2016) - Dinh-Nguyen, M. T.; Delacourt, C.
Abstract : The solid electrolyte interphase (SEI) that forms at carbonaceous anodes makes Li-ion battery a viable technology because it inhibits solvent-decomposition reactions. However, passivation is never complete and SEI "leakage" appears as the main contributor to Li-ion battery aging. There has been a great deal of experiments focusing on the chemical analysis of SEIs over the past decades. Still, a direct evaluation of their passive character has not been much regarded. In this work, SEIs formed cathodically on glassy carbon electrodes are characterized using the rotating disk electrode method and ferrocene/ferrocenium as a redox shuttle, as originally proposed in Tang and Newman [M. Tang and J. Newman, This journal, 158 (5), A530-A536 (2011)]. A comprehensive model is developed that accounts for transport of soluble redox species across the diffusion layer and the porous SEI as well as charge-transfer kinetics at the modified electrode surface. From a model analysis of electrodes with SEIs formed in various conditions, values of SEI porosity and effective rate constant of ferrocenium reduction are derived and discussed. First attempts are conducted to extend the method to SEIs formed at graphite composite electrodes. Preliminary results suggest SEIs are less passivating than those on glassy carbon.